European College of Phlebology guideline for truncal ablation. (March 2020) - Kürşat Bozkurt, A; Lawaetz, Martin; Danielsson, Gudmundur; Lazaris, Andreas M; Pavlovic, Milos; Olariu, Sorin; Rasmussen, Lars
Background: The purpose of the guideline was to achieve consensus in the care and treatment of patients with chronic venous disease, based on current evidence. Method: A systematic literature search was performed in PubMed, Embase, Cinahl, and the Cochrane library up until 1 February 2019. Additional relevant literature were added through checking of references. Level of evidence was graded through the GRADE scale and recommendations were concluded. Results: For the treatment of great and small saphenous vein reflux, endovenous ablation with laser or radiofrequency was recommended in preference to surgery or foam sclerotherapy. If tributaries are to be treated it should be done in the same procedure. Treatment with mecanicochemical ablation and glue can be used but we still need long term follow up results. Conclusion: For the treatment of truncal varicosities, endovenous ablation with laser or radiofrequency combined with phlebectomies is recommended before surgery or foam.